Critical Role of Jak2 in the Maintenance and Function of Adult Hematopoietic Stem Cells. (17th June 2014) - Akada, Hajime; Akada, Saeko; Hutchison, Robert E.; Sakamoto, Kazuhito; Wagner, Kay-Uwe; Mohi, Golam
Abstract : Jak2, a member of the Janus kinase family of nonreceptor protein tyrosine kinases, is activated in response to a variety of cytokines, and functions in survival and proliferation of cells. An activating JAK2V617F mutation has been found in most patients with myeloproliferative neoplasms, and patients treated with Jak2 inhibitors show significant hematopoietic toxicities. However, the role of Jak2 in adult hematopoietic stem cells (HSCs) has not been clearly elucidated. Using a conditional Jak2 knockout allele, we have found that Jak2 deletion results in rapid loss of HSCs/progenitors leading to bone marrow failure and early lethality in adult mice. Jak2 deficiency causes marked impairment in HSC function, and the mutant HSCs are severely defective in reconstituting hematopoiesis in recipient animals. Jak2 deficiency also causes significant apoptosis and loss of quiescence in HSC-enriched LSK (Lin − Sca-1 + c-Kit + ) cells. Jak2-deficient LSK cells exhibit elevated reactive oxygen species levels and enhanced p38 MAPK activation. Mutant LSK cells also show defective Stat5, Erk, and Akt activation in response to thrombopoietin and stem cell factor. Gene expression analysis reveals significant downregulation of genes related to HSC quiescence and self-renewal in Jak2-deficient LSK cells. These data suggest that Jak2 plays a critical role in the maintenance and function of adult HSCs. Stem Cells 2014;32:1878–1889